2012
DOI: 10.1155/2012/197809
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in theIn VitroFermentability of Short Carbohydrates in Static Faecal Batch Cultures

Abstract: In recent years, research has focused on the positive effects of prebiotics on intestinal health and gut microbiota. The relationship between their chemical structure and their fermentation pattern by human intestinal microbiota is still not well understood. The aim of this study was to improve understanding of this relationship and identify factors that may be used to design galactooligosaccharides that reach more distal regions than commercial prebiotics which mainly target the proximal colon. The following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…The reasons for this selective increase in butyrate production with α(1-1) glycosidic bond configuration are not clear and warrant further investigation. In another study, diglucose α(1-4) and diglucose α(1-6) linkages led to non-significant increases in propionate and butyrate production [ 21 ]. However, comparisons between these studies and the present study are difficult to interpret because of their short fermentation duration and the low number of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The reasons for this selective increase in butyrate production with α(1-1) glycosidic bond configuration are not clear and warrant further investigation. In another study, diglucose α(1-4) and diglucose α(1-6) linkages led to non-significant increases in propionate and butyrate production [ 21 ]. However, comparisons between these studies and the present study are difficult to interpret because of their short fermentation duration and the low number of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…With 10 incubations the study was powered (0.8) to observe a 9.5 mM (0.47 mmol/g carbohydrate/day) difference in propionate production, an additional 5 incubations provided the power (0.8) to observe a 7.5 mM (0.37 mmol/g carbohydrate/day) difference in propionate production. Previous in vitro fermentation studies have shown similar differences in propionate production between different fibers [ 35 ] and between simple sugars [ 21 ].…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…When consumed, GOS reach the distal colon similar to HMOs where they are degraded by resident bacteria28, promoting the growth of bacterial families, including Bifidobacteriaceae and Bacteroidaceae , in the intestine of infants in a similar ratio to that found in the gut microbiota of breast-fed infants. GOS are very complex mixtures25, and very little is known about what components within GOS offer the same HMOs-like effects.…”
mentioning
confidence: 99%